Development of Digital Mind Mapping Based on Imrithi for Nahwu Learning at Islamic Boarding School - Abdillah, Ayub; Kholisin; Imam Asrori; Seraiaia Yassine (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2025)
The teaching of nahwu in Islamic boarding schools often still relies on traditional methods, which tend to be monotonous. This research aimed to develop digital mind mapping materials based on the Nazham Imrithi text as an alternative learning medium that is more interactive and effective. The research subjects were female students at Al Ishlahiyah Female Islamic Boarding School. The development method used was the ADDIE model (Analyze, Design, Develop, Implement, Evaluation). The results of this research and development showed that the validity score from content experts was 3.9, while the validity score from media experts was 4.1, both of which fall into the good category and are feasible for use. The practicality level based on teachers' responses was 4.2, which falls into the agree category, while the practicality level based on students' responses was 3,9 or agree. Thus, the interactive media developed by the researcher is considered both feasible and practical for use.